RUSSIA'S PARTICIPATION IN MULTILATERAL MECHANISMS IN EAST ASIA - N. V. Stapran (Vestnik MGIMO-Universiteta)
After the end of the Cold War Russia has significantly increased its participation in multilateral mechanisms in the Asia-Pacific region and is clearly trying to become a significant player in regional institution-building. For two post-Cold War Russia decades was involved in almost all the basic mechanisms of multilateral cooperation in the Asia-Pacific region. However, often Russia isn't perceived by Asian partners as an equal participant in the Asia-Pacific region, it is felt particularly in the area of multilateral economic cooperation. Russia's entry into the WTO (2011) and the formation of the Common Economic stimulated Russia's engagement in multilateral economic structures. Russia's inclusion in the negotiating framework of ASEM (2010) and EAS (2011) perceives that Asian countries are willing to see Russia as a full member not only in regional processes, but also globally. The main stimulus for the revision of the Asian direction of foreign policy and the role of Siberia and the Far East appears during APEC summit in Vladivostok in 2012. The APEC summit demonstrated the geostrategic importance of the development of the Russian Far East and Siberia, as a key element of Russia's inclusion in the mechanisms of regional cooperation, on the other hand, it became clear that without the participation of foreign partners effective development of the Far Eastern territories is hardly possible. Large-scale investment and infrastructure projects in the Far East has already significantly revived the situation in the region opening new opportunities for multilateral cooperation.